ผลของการสอนตามแนวคิดความเชื่อด้านสุขภาพและการมีส่วนร่วมของผู้ดูแลต่อพฤติกรรมการดูแลสุขภาพของเด็กวัยเรียนโรคหัวใจพิการแต่กำเนิด - จันทร์จุรีย์ ถือทอง (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The purpose of this quasi-experimental research was to study the effect of using teaching according to health belief concept and caregiver participation on health care behaviors of school-aged children with congenital heart disease. The child health belief model of Bush & Iannotti (1990) and family participation concept of Friedman (2003) were used to guide this study. Subjects were 40 school aged children 7-12 years with congenital heart disease who received treatment at out patient Department, Chulalongkorn hospital. They were assigned to control group and experimental group, 20 for each. Age of children, severity of disease and caregiver education and salary were matched. The control group received routine teaching from the professional nurse and the experimental group received the teaching according to health belief concept and caregiver participation. Health care behaviors assessed using questionnaire developed by the investigator. The questionnaire was tested for reliability using Cronbach’s coefficient (alpha = .79).Data were analyzed using t-test statistics. Major findings were as follows:1. Health care behaviors of school-aged children with congenital heart disease after receiving the teaching according to health belief concept and caregiver participation were significantly higher than those before. (p< .05) 2. Health care behaviors of school-aged children with congenital heart disease experimental group received the teaching according to health belief concept and caregiver participation were significantly higher than those of the control group received routine teaching from the professional nurse (p< .05)